2023
DOI: 10.1371/journal.pntd.0010984
|View full text |Cite
|
Sign up to set email alerts
|

Soil-transmitted helminth surveillance in Benin: A mixed-methods analysis of factors influencing non-participation in longitudinal surveillance activities

Abstract: Background Despite the significant success of deworming programs in reducing morbidity due to soil-transmitted helminth (STH) infections globally, efforts to achieve elimination of STH as a public health problem or to potentially interrupt transmission will require improving and intensifying surveillance. However, non-participation in surveillance threatens the ability of programs to adequately monitor program status and limited research has been conducted to investigate drivers of non-participation in stool-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…The participants of this study identified several barriers to adults’ participation in STH cMDA, such as adults’ mistrust of cMDA programs; fear of side effects of deworming, specifically if they are on concomitant medication; their perceived low risk to STH infections; and their absence during drug distribution, similar to barriers reported by the adults in MDA programs for STH and lymphatic filariasis (LF) in India, Benin, Malawi, and Tanzania. 20 , 23 26 Similarly, as suggested in other studies, the adolescents in this study believed that community outreach activities, involvement of village leaders and government health workers, treatment delivery by trusted drug distributors at a time and day convenient to the community members, and counseling during drug distribution would facilitate adult participation in cMDA. 27 …”
Section: Discussionsupporting
confidence: 72%
“…The participants of this study identified several barriers to adults’ participation in STH cMDA, such as adults’ mistrust of cMDA programs; fear of side effects of deworming, specifically if they are on concomitant medication; their perceived low risk to STH infections; and their absence during drug distribution, similar to barriers reported by the adults in MDA programs for STH and lymphatic filariasis (LF) in India, Benin, Malawi, and Tanzania. 20 , 23 26 Similarly, as suggested in other studies, the adolescents in this study believed that community outreach activities, involvement of village leaders and government health workers, treatment delivery by trusted drug distributors at a time and day convenient to the community members, and counseling during drug distribution would facilitate adult participation in cMDA. 27 …”
Section: Discussionsupporting
confidence: 72%
“…Soil-transmitted helminths (STH) belong to a group of neglected tropical diseases, which occur primarily in low-and middle-income countries across tropical and subtropical regions, and disproportionately affect low-income communities [1]. Globally, World Health Organization (WHO) estimates more than 1.5 billion (24% of the world population) people are infected with STHs in Africa, Asia, and Latin America [1][2][3]. Over 260 million preschool-age and 654 million school-age children live in areas where STH transmission is very high [1].…”
Section: Introductionmentioning
confidence: 99%